The effect of the Varroa destructor mite on hemolymph indicators of honey bees - Назаренко, О. С. (Scientific Progress & Innovations, 2018)
Analysis of the cellular composition of hemolymph is of great importance for assessing the physiological state of the bees. This is due to the fact that the composition of hemocytes of the hemolymph is variable, which depends on the age, season of the year, as well as in various diseases and the impact of adverse environmental factors. Studies of domestic scientists have shown that varroosis of bees significantly affects the hemolymph indices of honeybees. A hemolymph like the blood of animals shows not only the physiological, but also the pathological changes in the body of the bees. So scientific and practical interest is the study of the effect of varooza invasion on the body of honey bees, taking into account their age. In this connection, the purpose of the study was to determine the effect of the Varroa destructor mite on the composition of hemolymph of infested bees. The studies were being conducted during 2018 in the conditions of a private apiary in the Grebenkovsky district of the Poltava region. The object of the study were the bees of the same age, which were obtained by incubating of the printed brood. 8 groups were formed: 4 research groups which bees affected by the Varroa destructor mite of different ages (one, four, eight and twelve days of age) and 4 control groups which bees were free from a mite of similar age. From each group were taken 15 hemolymph samples (120 samples in total). According to the results of the conducted research, it has been established that the Varroa destructor mites significantly affect the physiological state of the infested bees, namely, the indicators of the hemolymph formed elements. Invasion is revealed by a decrease in progenitor cells (proleukocyte and growth of phagocytes), which indicate the activation of the immune system of bees, as well as the toxic effect of invasion of pathogens. It has been proven that the age of bees has a significant effect on the bees' immune response to varroosis, as evidenced by the dynamics of secretory cells (the spherulites in bees hemolymph). It was found that the age ratio of hemolymph in bees over varroosis significantly increases (up to 28.6%), which indicates the depletion of the insects’ body. Prospects for further research is to determine the effect of Varroa destructor on the state of the fat body and the lifespan of honeybees.